Preparation method and application of protective layer material for suppressing short circuit in lithium battery
By using a protective layer material composed of a positive electrode material, a solid electrolyte and an oxide-based negative electrode material in a lithium battery, the lithium metal dendrites are consumed, the short circuit problem within the lithium battery is solved, the safety and cycle life of the battery are improved, and Provides higher energy density and stability.
Patent Information
- Application Number
- CN202410656696.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-24
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-05-24
Smart Images

Figure CN118610689B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of new energy materials, and relates to a method for preparing a protective layer material capable of suppressing short circuits within lithium batteries, and specifically to a method for preparing a battery protective layer material capable of consuming lithium metal dendrites through chemical reactions, and its application in batteries. Background Art
[0002] As a secondary rechargeable power source, lithium-ion batteries have the advantages of high voltage, high specific energy, high output power, low self-discharge, wide application scenarios, no memory effect and easy recycling. They are regarded as one of the most promising electrochemical energy storage technologies and are increasingly used in various portable devices and aerospace fields. With the growing demand for full electrification of various devices, battery safety has received more and more attention.
[0003] Whether it is a lithium-ion battery with graphite as the negative electrode or a battery with lithium metal as the negative electrode, it faces the phenomenon of lithium precipitation at the negative electrode when charging at a high rate. In severe cases, lithium dendrites will form, which not only limits the fast charging performance of the battery, but also affects the safety of the battery. Lithium dendrites pierce the diaphragm and contact the positive electrode, forming a micro short circuit or soft short circuit in the battery. Long-term accumulation will cause a hard short circuit in the battery, causing battery combustion, explosion and other safety problems. The use of solid electrolytes can alleviate the battery short circuit problem to a certain extent, but solid-state batteries face challenges such as insufficient electrolyte conductivity and poor interface stability. Summary of the invention
[0004] In response to the internal short circuit problem caused by lithium dendrites piercing the diaphragm, the present invention provides a method for preparing a protective layer material that can be used to suppress the internal short circuit of a lithium battery by consuming lithium metal dendrites through a chemical reaction and its application. The protective layer material prepared by the method is composed of a positive electrode material, a solid electrolyte and an oxide-based negative electrode material, which is coated on the positive electrode side and directly contacts the diaphragm. When lithium dendrites grow to the positive electrode side during the cycle, the protective layer material consumes the lithium metal to avoid direct contact between the positive and negative electrodes to form an internal short circuit, thereby improving the safety and cycle life of the battery.
[0005] The objective of the present invention is achieved through the following technical solutions:
[0006] A method for preparing a protective layer material that can be used to suppress internal short circuits in lithium batteries comprises the following steps:
[0007] Step 1: Preparation of cathode material precursor:
[0008] Step 1: add 0.5-10g of lithium source and 0.5-10g of iron source to 50-150ml of hydrothermal solvent, stir vigorously at a speed of 800-2000r / min for 0.5-4h to mix evenly, then slowly add 0.5-10g of phosphoric acid source, and stir vigorously at the same time, at this time, the solution forms a nano-scale precipitate, which is a complex of lithium source, iron source and phosphoric acid source;
[0009] Step 12: Transfer the solution in step 11 to a reaction kettle, seal it, and perform a hydrothermal reaction at 120-200° C. for 5-15 hours, then centrifuge and wash it with ethanol for 1-3 times, and vacuum dry it at 45-100° C. for 5-24 hours to obtain a cathode material precursor;
[0010] Step 2: Preparation of lithium iron phosphate precursor coated with lithium aluminum titanium phosphate precursor:
[0011] Step 21: add a lithium source, a phosphate source, a titanium source and an aluminum source in a total mass of 1 to 20 g and a molar ratio of 0.1 to 5: 0.1 to 5: 0.1 to 5: 0.1 to 5 to 10 to 50 ml of an organic solution, and ball mill at a speed of 300 to 600 r / min for 5 to 60 min;
[0012] Step 22: Add the gel precursor and the cathode material precursor obtained in step 1, and continue stirring at a speed of 500 to 1500 r / min for 5 to 60 min at 40 to 80 ° C to obtain solid electrolyte precursor particles, which contain polymer gel particles formed by the gel precursor and cathode material precursor particles to form secondary particles, i.e., lithium iron phosphate precursor coated with lithium titanium aluminum phosphate precursor;
[0013] Step 3: Preparation of porous lithium iron phosphate coated with lithium aluminum titanium phosphate precursor:
[0014] Step 3: sinter the secondary particles obtained in step 2 at 200-500° C. for 2-6 hours under high-purity argon conditions, during which the polymer gel particles decompose to form micron-sized pores;
[0015] Step 32: Under high-purity argon conditions, the temperature is raised to 500-800° C. and sintered for 4-10 hours. At this time, the cathode material precursor is sintered into a cathode active material and is wrapped by the solid electrolyte precursor;
[0016] Step 33: Transfer to a muffle furnace and sinter at 900-1300° C. for 0.5-2 h under air conditions, at which time the solid electrolyte precursor is sintered into a lithium titanium aluminum phosphate electrolyte to obtain a porous lithium iron phosphate coated with the lithium titanium aluminum phosphate precursor;
[0017] Step 4: Preparation of protective layer materials:
[0018] Step 41: Add the lithium source and the titanium source with a total mass of 0.5-10 g and a molar ratio of 0.1-2:0.1-2 to 10-100 ml of a hydrothermal solvent, and stir vigorously at 500-1500 r / min for 0.5-2 h to form a uniform suspension;
[0019] Step 42: Immerse the porous lithium iron phosphate coated with the lithium aluminum titanium phosphate precursor obtained in step 3 into the suspension of step 41 and mix evenly. After sealing, perform hydrothermal reaction at 100-200° C. for 5-15 hours. At this time, the lithium source and the titanium source nucleate in the pores inside the secondary particles to form an oxide-based negative electrode material precursor, which eventually fills the entire pores.
[0020] Step 43: Wash by centrifugation with ethanol for 1 to 3 times, and dry under vacuum at 40 to 80°C for 2 to 15 hours;
[0021] Step 44: Place the dried material under high-purity oxygen conditions and sinter at 500-800° C. for 2-8 hours to obtain a protective layer material that can react to lithium metal dendrites. The protective layer material can be used in lithium batteries.
[0022] Compared with the prior art, the present invention has the following advantages:
[0023] 1. The present invention ingeniously creates a new material with a secondary particle structure ( Figure 1 ), the secondary particles have positive electrode primary particles, solid electrolyte and negative electrode primary particles. The solid electrolyte separates the positive and negative electrode particles. The positive electrode particles provide capacity when the battery is charged and discharged, and the solid electrolyte can improve the overall utilization efficiency of the battery. The negative electrode material can react to remove lithium metal dendrites ( Figure 2 and Figure 3 ), thereby improving the safety of the battery.
[0024] 2. The protective layer material provided by the present invention contains positive electrode material inside, so it can provide additional capacity for the battery. Compared with the traditional ceramic diaphragm with inert material, the battery assembled with the protective layer material can provide higher energy density, such as Figure 4 shown.
[0025] 3. The protective layer material provided by the present invention can replace the ceramic coating of the ceramic diaphragm ( Figure 5 ), which can not only improve the overall stability of the battery, but also alleviate the internal short circuit problem of the lithium battery and improve the cycle stability of the battery ( Figure 6 ) and security.
[0026] 4. The protective layer material provided by the present invention can be coated on the surface of the positive electrode and is fully compatible with the existing lithium battery preparation process. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 Schematic diagram of the preparation process of protective layer materials;
[0028] Figure 2 Schematic diagram of the process of converting lithium iron phosphate coated with a porous lithium titanium aluminum phosphate precursor into a protective layer material;
[0029] Figure 3 This is a scanning electron microscope image of the protective layer material;
[0030] Figure 4 The charge and discharge curve of the battery with protective layer material;
[0031] Figure 5 A schematic diagram of a battery structure with a protective layer material;
[0032] Figure 6 The cycling performance of the battery with protective layer material. DETAILED DESCRIPTION
[0033] The technical solution of the present invention is further described below in conjunction with the accompanying drawings, but is not limited thereto. Any modification or equivalent replacement of the technical solution of the present invention without departing from the spirit and scope of the technical solution of the present invention should be included in the protection scope of the present invention.
[0034] The present invention provides a method for preparing a protective layer material that can be used to suppress short circuits in lithium batteries. The protective layer material has particles that are composited from a positive electrode material, a solid electrolyte, and an oxide-based negative electrode material. The structure is that primary particles of the positive electrode material and primary particles of the negative electrode material are evenly dispersed and are respectively wrapped by the solid electrolyte to form integral secondary particles, such as Figure 1 As shown, the specific preparation steps are as follows:
[0035] Step 1: Preparation of cathode material precursor:
[0036] Step 1: Add 0.5-10g of lithium source and 0.5-10g of iron source to 50-150ml of hydrothermal solvent, stir vigorously at a speed of 800-2000r / min for 0.5-4h to mix evenly, then slowly add 0.5-10g of phosphoric acid source, and stir vigorously at the same time. At this time, the solution forms a nano-scale precipitate, which is a composite of lithium source, iron source and phosphoric acid source, wherein:
[0037] The lithium source is one of lithium phosphate (Li3PO4), lithium acetate (CH3COOLi), lithium hydroxide (LiOH), lithium lactate (C3H5O3·Li), lithium borohydride (LiBH4), lithium oxalate (C2O4Li2), lithium citrate tetrahydrate (C6H5Li3O7·4H2O), lithium carbonate (Li2CO3) or a derivative thereof;
[0038] The iron source is hydrated ferric sulfate (FeSO4·xH2O), hydrated ammonium ferrous sulfate ((NH4)2Fe(SO4)2·6H2O), ferric pyrophosphate (Fe4(P2O7)3), ferric phosphate (FePO4), ferric acetate (C4H6O4Fe), ferric citrate (C6H 11 FeNO7);
[0039] The hydrothermal solvent is one of ethanol, ethylene glycol, glycerol, isopropanol, water, and n-butanol;
[0040] The phosphoric acid source is one of ammonium dihydrogen phosphate (NH4H2PO4), lithium dihydrogen phosphate (LiH2PO4), triethyl phosphate ((C2H5)3PO4), and phosphoric acid;
[0041] Step 12: Transfer the solution in step 11 to a reaction kettle, seal it, and perform a hydrothermal reaction at 120-200° C. for 5-15 hours, then centrifuge and wash it with ethanol for 1-3 times, and vacuum dry it at 45-100° C. for 5-24 hours to obtain a cathode material precursor;
[0042] Step 2: Preparation of lithium iron phosphate precursor coated with lithium aluminum titanium phosphate precursor:
[0043] Step 21: Add lithium source, phosphate source, titanium source and aluminum source in a total mass of 1 to 20 g and a molar ratio of 0.1 to 5: 0.1 to 5: 0.1 to 5: 0.1 to 5 to 10 to 50 ml of organic solution, and ball mill at a speed of 300 to 600 r / min for 5 to 60 min, wherein:
[0044] The organic solvent is one of ethanol, methanol and isopropanol;
[0045] The lithium source is one of lithium phosphate (Li3PO4), lithium acetate (CH3COOLi), lithium hydroxide (LiOH), lithium lactate (C3H5O3·Li), lithium borohydride (LiBH4), lithium oxalate (C2O4Li2), lithium citrate tetrahydrate (C6H5Li3O7·4H2O), lithium carbonate (Li2CO3) or a derivative thereof;
[0046] The phosphoric acid source is one of ammonium dihydrogen phosphate (NH4H2PO4), lithium dihydrogen phosphate (LiH2PO4), triethyl phosphate ((C2H5)3PO4), and phosphoric acid;
[0047] The titanium source is one of tetrabutyl titanate and titanium phosphate;
[0048] The aluminum source is one of aluminum hydroxide, aluminum oxide, and aluminum chloride;
[0049] Step 22: Add the gel precursor and the cathode material precursor obtained in step 1, and continue stirring at a speed of 500 to 1500 r / min for 5 to 60 min at 40 to 80 ° C to obtain solid electrolyte precursor particles, which contain polymer gel particles formed by the gel precursor and cathode material precursor particles to form secondary particles, i.e., lithium iron phosphate precursor coated with lithium titanium aluminum phosphate precursor, wherein:
[0050] The gel precursor is one of a mixture of polyethylene glycol diacrylate (PEGDA) and propylene carbonate (PC) and a mixture of pentaerythritol tetraacrylate (PETEA) and polyethylene glycol (PEG-400), wherein the mixing ratio of PEGDA to PC is 1:1, and the mixing ratio of PETEA to PEG-400 is 1:1;
[0051] Step 3: Preparation of porous lithium iron phosphate coated with lithium aluminum titanium phosphate precursor:
[0052] Step 3: sinter the secondary particles obtained in step 2 at 200-500° C. for 2-6 hours under high-purity argon conditions, during which the polymer gel particles decompose to form micron-sized pores;
[0053] Step 32: Under high-purity argon conditions, the temperature is raised to 500-800° C. and sintered for 4-10 hours. At this time, the cathode material precursor is sintered into a cathode active material and is wrapped by the solid electrolyte precursor;
[0054] Step 3: Transfer to a muffle furnace and sinter at 900-1300°C for 0.5-2h under air conditions. At this time, the solid electrolyte precursor is sintered into a lithium titanium aluminum phosphate electrolyte to obtain a porous lithium iron phosphate coated with the lithium titanium aluminum phosphate precursor. Figure 2 As shown;
[0055] Step 4: Preparation of protective layer materials:
[0056] Step 41: Add the lithium source and titanium source with a total mass of 0.5-10 g and a molar ratio of 0.1-2:0.1-2 to 10-100 ml of a hydrothermal solvent, and stir vigorously at 500-1500 r / min for 0.5-2 h to form a uniform suspension, wherein:
[0057] The lithium source is one of lithium phosphate (Li3PO4), lithium acetate (CH3COOLi), lithium hydroxide (LiOH), lithium lactate (C3H5O3·Li), lithium borohydride (LiBH4), lithium oxalate (C2O4Li2), lithium citrate tetrahydrate (C6H5Li3O7·4H2O), lithium carbonate (Li2CO3) or a derivative thereof;
[0058] The titanium source is one of tetrabutyl titanate and titanium phosphate;
[0059] The hydrothermal solvent is one of ethanol, ethylene glycol, glycerol, isopropanol, water, and n-butanol;
[0060] Step 42: Immerse the porous lithium iron phosphate coated with the lithium aluminum titanium phosphate precursor obtained in step 3 into the suspension of step 41 and mix evenly. After sealing, perform hydrothermal reaction at 100-200° C. for 5-15 hours. At this time, the lithium source and the titanium source nucleate in the pores inside the secondary particles to form an oxide-based negative electrode material precursor, which eventually fills the entire pores.
[0061] Step 43: Wash by centrifugation with ethanol for 1 to 3 times, and dry under vacuum at 40 to 80°C for 2 to 15 hours;
[0062] Step 4: Place the dried material under high-purity oxygen conditions and sinter at 500-800°C for 2-8 hours to obtain a protective layer material that can react to lithium metal dendrites. The morphology is as follows: Figure 3 shown.
[0063] The protective layer material for suppressing short circuit in lithium battery prepared by the above method can be used in lithium battery, and can be sprayed on the surface of diaphragm to replace the diaphragm ceramic coating or coated on the surface of positive electrode, wherein:
[0064] The specific method of spraying the protective layer material on the surface of the diaphragm to replace the diaphragm ceramic coating and applying it in the lithium battery is as follows:
[0065] Step (1) mixing the protective layer material, the binder and the solvent in a mass ratio of 80-100:1-10:80-180 to form an electrode slurry;
[0066] Step (2) The electrode slurry is mixed in a planetary agitator for 10 to 60 minutes at a rotation speed of 700 to 1000 r / min to obtain a protective layer material slurry;
[0067] Step (3) pouring the protective layer material slurry into an ultrasonic sprayer, spraying it evenly on the PE base film, and obtaining a ceramic diaphragm coated with the protective layer material after drying;
[0068] Step (4) assembles the ceramic diaphragm coated with the protective layer material with commercial positive electrode material, negative electrode material and electrolyte into a full battery. The protective layer material can provide a part of the capacity, and the battery assembled with the protective layer material can provide more capacity.
[0069] The specific method of coating the protective layer material on the positive electrode surface and applying it in a lithium battery is as follows:
[0070] Step (1) mixing the protective layer material, the binder and the solvent in a mass ratio of 80-100:1-10:80-180 to form an electrode slurry;
[0071] Step (2) The electrode slurry is mixed in a planetary agitator for 10 to 60 minutes at a rotation speed of 700 to 1000 r / min to obtain a protective layer material slurry;
[0072] Step (3) coating the protective layer material slurry on the commercial positive electrode sheet, drying, and rolling to obtain a low-temperature battery positive electrode sheet;
[0073] Step (4) After punching the positive electrode sheet, it is assembled with the separator, electrolyte, graphite negative electrode or lithium metal negative electrode into a full battery, the structure of which is as follows: Figure 5 As shown, the protective layer material can extend the cycle performance of lithium metal batteries and greatly improve the internal short circuit situation compared to ordinary batteries.
[0074] Embodiment 1:
[0075] This embodiment provides a method for preparing a protective layer material that can be used for a structural battery, the method comprising the following steps:
[0076] Step 1: Preparation of cathode material precursor:
[0077] Add 2.8g lithium carbonate and 4.5g hydrated ferric sulfate to 60ml ethylene glycol, stir vigorously at 1500r / min for 1h, then slowly add 4.5g lithium dihydrogen phosphate while stirring vigorously; transfer the above solution to a reactor, seal it, and carry out hydrothermal reaction at 170°C for 12h, then wash it by centrifugation with ethanol for 3 times, and vacuum dry it at 80°C for 12h to obtain a positive electrode material precursor.
[0078] Step 2: Preparation of lithium iron phosphate precursor coated with lithium aluminum titanium phosphate precursor:
[0079] Lithium phosphate, lithium hydroxide, ammonium dihydrogen phosphate, tetrabutyl titanate and aluminum oxide are added to 40 ml of ethanol in a total mass of 8 g and a molar ratio of 1:0.3:1:3, and ball milled at a speed of 400 r / min for 30 minutes; then 3.5 g of a gel precursor prepared by mixing pentaerythritol tetraacrylate and polyethylene glycol in a ratio of 1:1 and 3.5 g of the positive electrode material precursor obtained in step 1 are added, and stirring is continued at 75°C and a speed of 1200 r / min for 30 minutes to form secondary particles, i.e., a lithium iron phosphate precursor coated with a lithium aluminum titanium phosphate precursor.
[0080] Step 3: Preparation of porous lithium iron phosphate coated with lithium aluminum titanium phosphate precursor:
[0081] The secondary particles obtained in step 2 are placed in high-purity argon conditions and sintered at 400°C for 3 hours; under high-purity argon conditions, the temperature is increased to 650°C and sintered for 6 hours; transferred to a muffle furnace and sintered at 1100°C for 1.5 hours under air conditions to obtain porous lithium iron phosphate coated with lithium titanium aluminum phosphate precursor.
[0082] Step 4: Preparation of protective layer materials:
[0083] Lithium hydroxide and tetrabutyl titanate were added to ethylene glycol with a total mass of 5 g and a molar ratio of 0.5:1.5, and stirred vigorously at 1000 r / min for 1 hour. Then, the porous lithium iron phosphate secondary particles coated with lithium aluminum titanium phosphate precursor were immersed in the suspension and mixed evenly. After sealing, the suspension was hydrothermally reacted at 180°C for 15 hours, and then centrifuged and washed 3 times with ethanol and vacuum dried at 60°C for 12 hours. The dried material was placed under high-purity oxygen conditions and sintered at 580°C for 2.5 hours to obtain a protective layer material that can react to lithium metal dendrites. Its morphology is as follows: Figure 3 shown.
[0084] The protective layer material prepared by the above method can be coated on the surface of the positive electrode and used in lithium batteries. The specific method is as follows:
[0085] The protective layer material, the binder and the solvent are mixed in a mass ratio of 96:4:120 to form an electrode slurry; the electrode slurry is mixed in a planetary agitator for 40 minutes at a speed of 800r / min to obtain a protective layer material slurry; the protective layer material slurry is coated on a commercial positive electrode sheet, dried, and rolled to obtain a low-temperature battery positive electrode sheet; after the positive electrode sheet is punched, it is assembled with a separator, an electrolyte, a graphite negative electrode or a lithium metal negative electrode into a full battery, the structure of which is as follows Figure 5 As shown, the protective layer material can prolong the cycle performance of lithium metal batteries and greatly improve the internal short circuit situation compared to ordinary batteries ( Figure 6 ).
[0086] Embodiment 2:
[0087] This embodiment provides a method for preparing a high-strength electrolyte that can be used in a structural battery, the method comprising the following steps:
[0088] Step 1: Preparation of cathode material precursor:
[0089] 3.2 g of lithium hydroxide and 5.4 g of hydrated ferric sulfate were added to 80 ml of ethylene glycol, and stirred vigorously at a speed of 1500 r / min for 1 hour to mix them evenly. Then 6 g of phosphoric acid was slowly introduced while stirring vigorously. The above solution was transferred to a reactor, sealed, and a hydrothermal reaction was carried out at 170°C for 9 hours. Then, the reactor was centrifuged and washed three times with ethanol, and vacuum dried at 100°C for 15 hours to obtain a positive electrode material precursor.
[0090] Step 2: Preparation of lithium iron phosphate precursor coated with lithium aluminum titanium phosphate precursor:
[0091] Lithium hydroxide, triethyl phosphate, tetrabutyl titanate and aluminum hydroxide were added to 45 ml of organic solution in a total mass of 8 g and a molar ratio of 1.3:0.6:1:4, and ball milled at a speed of 350 r / min for 30 min; then 5 g of a gel precursor prepared by mixing polyethylene glycol diacrylate and propylene carbonate in a ratio of 1:1 and 3.5 g of the positive electrode material precursor obtained in step 1 were added, and stirring was continued at 70°C and a speed of 1000 r / min for 30 min.
[0092] Step 3: Preparation of porous lithium iron phosphate coated with lithium aluminum titanium phosphate precursor:
[0093] The secondary particles obtained in step 2 are placed in high-purity argon conditions and sintered at 380°C for 5 hours; under high-purity argon conditions, the temperature is increased to 650°C and sintered for 6 hours; transferred to a muffle furnace and sintered at 1050°C for 1 hour under air conditions to obtain porous lithium iron phosphate coated with lithium titanium aluminum phosphate precursor, such as Figure 2 shown.
[0094] Step 4: Preparation of protective layer materials:
[0095] Lithium hydroxide and tetrabutyl titanate were added to 35 ml of ethylene glycol at a total mass of 3 g and a molar ratio of 0.5:1.5, and vigorously stirred at 1000 r / min for 0.5 h. Then, the porous lithium iron phosphate secondary particles coated with lithium aluminum titanium phosphate precursor were immersed in the suspension. After mixing evenly, the mixture was sealed and hydrothermally reacted at 185 ° C for 12 h. Then, the mixture was centrifuged and washed 3 times with ethanol and vacuum dried at 60 ° C for 12 h. The dried material was placed in high-purity oxygen conditions and sintered at 550 ° C for 3 h to obtain a protective layer material that can react to lithium metal dendrites. Its morphology is as follows: Figure 3 shown.
[0096] The protective layer material prepared by the above method can be sprayed on the surface of the diaphragm to replace the diaphragm ceramic coating and used in lithium batteries. The specific method is as follows:
[0097] The protective layer material, binder and solvent are mixed in a mass ratio of 93:7:120 to form an electrode slurry; the electrode slurry is mixed in a planetary agitator for 40 minutes at a speed of 800r / min to obtain a protective layer material slurry; the protective layer material slurry is poured into an ultrasonic sprayer and sprayed evenly on the PE base film, and after drying, a ceramic diaphragm coated with the protective layer material is obtained, which is then assembled into a full battery with commercial positive electrode materials, negative electrode materials and electrolytes. The protective layer material can provide a portion of the capacity, such as Figure 4As shown, batteries assembled with protective layer materials can provide more capacity.
Claims
1. A method for preparing a protective layer material that can be used to suppress short circuits in lithium batteries, characterized in that The method comprises the following steps: Step 1: Preparation of cathode material precursor: Step 1: add 0.5-10g of lithium source and 0.5-10g of iron source to 50-150ml of hydrothermal solvent, stir vigorously at a speed of 800-2000r / min for 0.5-4h to mix evenly, then slowly add 0.5-10g of phosphoric acid source, and stir vigorously at the same time, at this time, the solution forms a nano-scale precipitate, which is a complex of lithium source, iron source and phosphoric acid source; Step 12: Transfer the solution in step 11 to a reaction kettle, seal it, and perform a hydrothermal reaction at 120-200° C. for 5-15 hours, then centrifuge and wash it with ethanol for 1-3 times, and vacuum dry it at 45-100° C. for 5-24 hours to obtain a cathode material precursor; Step 2: Preparation of lithium iron phosphate precursor coated with lithium aluminum titanium phosphate precursor: Step 21: add a lithium source, a phosphate source, a titanium source and an aluminum source in a total mass of 1 to 20 g and a molar ratio of 0.1 to 5: 0.1 to 5: 0.1 to 5: 0.1 to 5 to 10 to 50 ml of an organic solution, and ball mill at a speed of 300 to 600 r / min for 5 to 60 min; Step 22: Add the gel precursor and the cathode material precursor obtained in step 1, and continue stirring at a speed of 500 to 1500 r / min for 5 to 60 min at 40 to 80 ° C to obtain solid electrolyte precursor particles, which contain polymer gel particles formed by the gel precursor and cathode material precursor particles to form secondary particles, i.e., lithium iron phosphate precursor coated with lithium titanium aluminum phosphate precursor; Step 3: Preparation of porous lithium iron phosphate coated with lithium aluminum titanium phosphate precursor: Step 3: sinter the secondary particles obtained in step 2 at 200-500° C. for 2-6 hours under high-purity argon conditions, during which the polymer gel particles decompose to form micron-sized pores; Step 32: Under high-purity argon conditions, the temperature is raised to 500-800° C. and sintered for 4-10 hours. At this time, the cathode material precursor is sintered into a cathode active material and is wrapped by the solid electrolyte precursor; Step 33: Transfer to a muffle furnace and sinter at 900-1300° C. for 0.5-2 h under air conditions, at which time the solid electrolyte precursor is sintered into a lithium titanium aluminum phosphate electrolyte to obtain a porous lithium iron phosphate coated with the lithium titanium aluminum phosphate precursor; Step 4: Preparation of protective layer materials: Step 41: Add the lithium source and the titanium source with a total mass of 0.5-10 g and a molar ratio of 0.1-2:0.1-2 to 10-100 ml of a hydrothermal solvent, and stir vigorously at 500-1500 r / min for 0.5-2 h to form a uniform suspension; Step 42: Immerse the porous lithium iron phosphate coated with the lithium aluminum titanium phosphate precursor obtained in step 3 into the suspension of step 41 and mix evenly. After sealing, perform hydrothermal reaction at 100-200° C. for 5-15 hours. At this time, the lithium source and the titanium source nucleate in the pores inside the secondary particles to form an oxide-based negative electrode material precursor, which eventually fills the entire pores. Step 43: Wash by centrifugation with ethanol for 1 to 3 times, and dry under vacuum at 40 to 80°C for 2 to 15 hours; Step 44: Place the dried material under high-purity oxygen conditions and sinter at 500-800° C. for 2-8 hours to obtain a protective layer material that can react with lithium metal dendrites.
2. The method for preparing a protective layer material for suppressing internal short circuit of a lithium battery according to claim 1, characterized in that In the step 1, the lithium source is one of lithium phosphate, lithium acetate, lithium hydroxide, lithium lactate, lithium borohydride, lithium oxalate, lithium citrate tetrahydrate, lithium carbonate or a derivative thereof; the iron source is one of hydrated ferric sulfate, hydrated ammonium ferrous sulfate, ferric pyrophosphate, ferric phosphate, ferric acetate, and ferric citrate; the hydrothermal solvent is one of ethanol, ethylene glycol, glycerol, isopropanol, water, and n-butanol; and the phosphoric acid source is one of diammonium phosphate, lithium dihydrogen phosphate, triethyl phosphate, and phosphoric acid.
3. The method for preparing a protective layer material for suppressing internal short circuit of a lithium battery according to claim 1, characterized in that In the step 2, the organic solvent is one of ethanol, methanol, and isopropanol; the lithium source is one of lithium phosphate, lithium acetate, lithium hydroxide, lithium lactate, lithium borohydride, lithium oxalate, lithium citrate tetrahydrate, and lithium carbonate, or a derivative thereof; the phosphate source is one of ammonium dihydrogen phosphate, lithium dihydrogen phosphate, triethyl phosphate, and phosphoric acid; the titanium source is one of tetrabutyl titanate and titanium phosphate; the aluminum source is one of aluminum hydroxide, aluminum oxide, and aluminum chloride; and the gel precursor is one of a mixed solution of polyethylene glycol diacrylate and propylene carbonate, or a mixed solution of pentaerythritol tetraacrylate and polyethylene glycol.
4. The method for preparing a protective layer material for suppressing internal short circuit of a lithium battery according to claim 3, characterized in that The mixing ratio of polyethylene glycol diacrylate to propylene carbonate is 1:1, and the mixing ratio of pentaerythritol tetraacrylate to polyethylene glycol is 1:
1.
5. The method for preparing a protective layer material for suppressing internal short circuit of a lithium battery according to claim 1, characterized in that In step 4, the lithium source is one of lithium phosphate, lithium acetate, lithium hydroxide, lithium lactate, lithium borohydride, lithium oxalate, lithium citrate tetrahydrate, and lithium carbonate, or a derivative thereof; the titanium source is one of tetrabutyl titanate and titanium phosphate; and the hydrothermal solvent is one of ethanol, ethylene glycol, glycerol, isopropanol, water, and n-butanol.
6. A protective layer material prepared by the method according to any one of claims 1 to 5 and used for suppressing internal short circuit in lithium batteries.
7. Use of a protective layer material prepared by the method according to any one of claims 1 to 5 and used for suppressing internal short circuit of a lithium battery in a lithium battery.
8. Use of the protective layer material for suppressing internal short circuit of a lithium battery according to claim 7 in a lithium battery, characterized in that The specific preparation method of the lithium battery is as follows: Step (1) mixing the protective layer material, the binder and the solvent in a mass ratio of 80-100:1-10:80-180 to form an electrode slurry; Step (2) The electrode slurry is mixed in a planetary agitator for 10 to 60 minutes at a rotation speed of 700 to 1000 r / min to obtain a protective layer material slurry; Step (3) pouring the protective layer material slurry into an ultrasonic sprayer, spraying it evenly on the PE base film, and obtaining a ceramic diaphragm coated with the protective layer material after drying; Step (4) assembles the ceramic diaphragm coated with the protective layer material with commercial positive electrode material, negative electrode material and electrolyte into a full battery.
9. Use of the protective layer material for suppressing internal short circuit of a lithium battery according to claim 7 in a lithium battery, characterized in that The specific preparation method of the lithium battery is as follows: Step (1) mixing the protective layer material, the binder and the solvent in a mass ratio of 80-100:1-10:80-180 to form an electrode slurry; Step (2) The electrode slurry is mixed in a planetary agitator for 10 to 60 minutes at a rotation speed of 700 to 1000 r / min to obtain a protective layer material slurry; Step (3) coating the protective layer material slurry on the commercial positive electrode sheet, drying, and rolling to obtain a low-temperature battery positive electrode sheet; Step (4) After the positive electrode sheet is punched, it is assembled with the separator, electrolyte, graphite negative electrode or lithium metal negative electrode into a full battery.
Citation Information
Patent Citations
Inorganic-organic nano composite solid electrolyte membrane and preparation method and application thereof
CN109638349A
Method of forming negative electrode protective layer through in-situ transfer
CN111697270A